THE MODERNIZATION OF EXECUTIVE POWER IN UZBEKISTAN DURING THE FIRST YEARS OF INDEPENDENCE - Jahongir Akramov Djumanazarovich; Maysara Ochilova Olimovna (Scholar Express Journal, 2023)
In the article were analyzed the processes of modernization of public administration in the early years of Independence of Uzbekistan. Based upon various scientific and political sources, the author elucidates the key trends and factors that determined the directions of implementation of the modernization of the executive power in Uzbekistan in the early years of Independence.
Keywords: Modernization; the executive power; the early years of Independence